COVID-19 vaccine-induced antibody and T-cell responses in immunosuppressed patients with inflammatory bowel disease after the third vaccine dose (VIP): a multicentre, prospective, case-control study. (November 2022) - Alexander, James L; Liu, Zhigang; Muñoz Sandoval, Diana; Reynolds, Catherine; Ibraheim, Hajir; Anandabaskaran, Sulak; Saifuddin, Aamir; Castro Seoane, Rocio; Anand, Nikhil; Nice, Rachel; Bewshea, Claire; D'Mello, Andrea; et al.
Summary: Background: COVID-19 vaccine-induced antibody responses are reduced in patients with inflammatory bowel disease (IBD) taking anti-TNF or tofacitinib after two vaccine doses. We sought to assess whether immunosuppressive treatments were associated with reduced antibody and T-cell responses in patients with IBD after a third vaccine dose. Methods: VIP was a multicentre, prospective, case-control study done in nine centres in the UK. We recruited immunosuppressed patients with IBD and non-immunosuppressed healthy individuals. All participants were aged 18 years or older. The healthy control group had no diagnosis of IBD and no current treatment with systemic immunosuppressive therapy for any other indication. The immunosuppressed patients with IBD had an established diagnosis of Crohn's disease, ulcerative colitis, or unclassified IBD using standard definitions of IBD, and were receiving established treatment with one of six immunosuppressive regimens for at least 12 weeks at the time of first dose of SARS-CoV-2 vaccination. All participants had to have received three doses of an approved COVID-19 vaccine. SARS-CoV-2 spike antibody binding and T-cell responses were measured in all participant groups. The primary outcome was anti-SARS-CoV-2 spike (S1 receptor binding domain [RBD]) antibody concentration 28–49 days after the third vaccine dose, adjusted by age, homologous versus heterologous vaccine schedule, and previous SARS-CoV-2 infection. The primary outcome was assessed in all participants with available data. Findings: Between Oct 18, 2021, and March 29, 2022, 352 participants were included in the study (thiopurine n=65, infliximab n=46, thiopurine plus infliximab combination therapy n=49, ustekinumab n=44, vedolizumab n=50, tofacitinib n=26, and healthy controls n=72). Geometric mean anti-SARS-CoV-2 S1 RBD antibody concentrations increased in all groups following a third vaccine dose, but were significantly lower in patients treated with infliximab (2736·8 U/mL [geometric SD 4·3]; p<0·0001), infliximab plus thiopurine (1818·3 U/mL [6·7]; p<0·0001), and tofacitinib (8071·5 U/mL [3·1]; p=0·0018) compared with the healthy control group (16 774·2 U/mL [2·6]). There were no significant differences in anti-SARS-CoV-2 S1 RBD antibody concentrations between the healthy control group and patients treated with thiopurine (12 019·7 U/mL [2·2]; p=0·099), ustekinumab (11 089·3 U/mL [2·8]; p=0·060), or vedolizumab (13 564·9 U/mL [2·4]; p=0·27). In multivariable modelling, lower anti-SARS-CoV-2 S1 RBD antibody concentrations were independently associated with infliximab (geometric mean ratio 0·15 [95% CI 0·11–0·21]; p<0·0001), tofacitinib (0·52 [CI 0·31–0·87]; p=0·012), and thiopurine (0·69 [0·51–0·95]; p=0·021), but not with ustekinumab (0·64 [0·39–1·06]; p=0·083), or vedolizumab (0·84 [0·54–1·30]; p=0·43). Previous SARS-CoV-2 infection (1·58 [1·22–2·05]; p=0·0006) was independently associated with higher anti-SARS-CoV-2 S1 RBD antibody concentrations and older age (0·88 [0·80–0·97]; p=0·0073) was independently associated with lower anti-SARS-CoV-2 S1 RBD antibody concentrations. Antigen-specific T-cell responses were similar in all groups, except for recipients of tofacitinib without evidence of previous infection, where T-cell responses were significantly reduced relative to healthy controls (p=0·021). Interpretation: A third dose of COVID-19 vaccine induced a boost in antibody binding in immunosuppressed patients with IBD, but these responses were reduced in patients taking infliximab, infliximab plus thiopurine, and tofacitinib. Tofacitinib was also associated with reduced T-cell responses. These findings support continued prioritisation of immunosuppressed groups for further vaccine booster dosing, particularly patients on anti-TNF and JAK inhibitors. Funding: Pfizer.